Wasmannia spp. (Hym., Formicidae) and insect damages to cocoa in Brazilian farms - De Souza, A. L B [UNESP]; Delabie, J. H C [UNESP]; Fowler, H. G. [UNESP] (My University, 1998)
Diagnostic insect damage to cocoa tree leaves and fruits were compared in situations with and without the presence of the little fire ants, Wasmannia auropunctata and the closely related and sympatric W. cf rochai. No significant differences in thrips, lepidopteran, or chrysomelid beetle damage to fruits, or to young and old leaves, were associated with these ants. However, significant increases of pseudococcids Planococcus citrii, associated with areas dominated by W. auropunctata, and to a lesser degree with W. cf rochai, were present. W. auropunctata has been reported to be a canopy mosaic dominant in cocoa farms, but the lack of reduced herbivore incidences and its lack of spatial permanence do not support favoring its populations for the management of phytophagous insect control.
Keywords: cocoa; insect; pest damage; potential biocontrol agent; Brazil; Chrysomelidae; Coleoptera; Formicidae; Homoptera; Hymenoptera; Lepidoptera; Planococcus citrii; Pseudococcidae; Thysanoptera; Wasmannia auropunctata; Wasmannia rochai